On the growing dangers of money in American democracy - Valentino Larcinese (EconPol Forum, 2024)
Democratic politics requires balancing a trade-off between equality and liberty. The current US campaign finance system, shaped largely by a series of Supreme Court decisions, has prioritized liberty, particularly through a questionable interpretation of money as speech. As a result of these rulings, money from individuals, corporations, and unions can flow to candidates without regulation, restriction, or, in some cases, transparency (through "dark money"). Although it is challenging to establish direct causal effects, growing evidence suggests that money does influence politicians. Moreover, through issue advertising, financial contributions shape the political agenda and influence the salience of certain issues in public debate. This dynamic has significant implications for the policies produced by the American political system. Wealthy donors tend to be substantially more conservative on economic issues than the general population. Campaign finance reform is one of the most pressing challenges facing the future of US democracy and requires urgent attention.
Keywords: 330